Os transportes e as dinâmicas territoriais no Amazonas - Thiago Oliveira Neto; Ricardo José Batista Nogueira (Confins)
The flow of cargo, people and information is increasingly intense and present in the most diverse places in the world and with the most varied technical contents available in the territories, allowing the establishment of spatial interactions involving multi-scale economic circuits between cities, districts and towns. Such dynamics are structured in different regions, in different ways. In this sense, this article seeks to present an overview of transportation in the state of Amazonas, highlighting the main modalities, the spatial organization and the performance of the State and companies in the establishment of infrastructures and the control or not of the circulation.